2020
DOI: 10.1021/acs.iecr.0c01130
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Modeling Investigation of Liquid-Induced Agglomeration in a Gas–Solid Fluidized Bed with Liquid Spray

Abstract: Particle agglomeration induced by liquid bridge force widely exists in industrial fluidization processes involving liquid spray. To understand the agglomeration mechanism, a cold-mode fluidized bed loaded with wax-coated graphite particles is constructed and heated by an electromagnetic induction method. In the experiments, the wet agglomerate mass is obtained online through the pressure drop measurement and the heat conservation relationship. Besides, an energy balance model is proposed based on the kinetic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Under this condition, the growth mode of particles changed from agglomeration to layer growth. The modified particle size was reduced with the inhibition of agglomeration, which was conducive to the uniform coating of modified particles on the surface [ 31 ]. Therefore, the mechanical strength of the composites also increased.…”
Section: Resultsmentioning
confidence: 99%
“…Under this condition, the growth mode of particles changed from agglomeration to layer growth. The modified particle size was reduced with the inhibition of agglomeration, which was conducive to the uniform coating of modified particles on the surface [ 31 ]. Therefore, the mechanical strength of the composites also increased.…”
Section: Resultsmentioning
confidence: 99%
“…Agglomerate breakup, which reduces the coke yield and operating issues, is promoted when agglomerates flow through highly turbulent regions. Models have been developed to predict agglomerate breakup, which occurs when the shear force from a gas bubble flowing near an agglomerate is greater than the liquid bridge force that keeps the wet agglomerate together. , Gas mixing affects the removal of vapors from the bed and vapor-phase cracking. Solid mixing affects vaporization kinetics because hot solids must be brought to liquid-rich regions to provide heat for product vaporization; good solid mixing is required to mitigate the cooling effect of liquid vaporization. If wet solids reach the stripping zone at the bottom of the reactor, valuable hydrocarbons may be lost to the cold coke return line (Figure ) and fouling of the stripper sheds (Figure ) is accelerated, which may lead to the premature shutdown of the coker. …”
Section: Reactormentioning
confidence: 99%
“…Models have been developed to predict agglomerate breakup, which occurs when the shear force from a gas bubble flowing near an agglomerate is greater than the liquid bridge force that keeps the wet agglomerate together. 50,51 Gas mixing affects the removal of vapors from the bed and vapor-phase cracking. Solid mixing affects vaporization kinetics because hot solids must be brought to liquid-rich regions to provide heat for product vaporization; good solid mixing is required to mitigate the cooling effect of liquid vaporization.…”
Section: Alternative Feedstocksmentioning
confidence: 99%
“…He et al [19] investigated the mineralogical characterization of various-sized bauxite samples using a dry-based fluidized-bed separator and obtained reasonable operating conditions for notably improved efficiency. Sun et al [20] designed a fluidized bed coupled with electromagnetic induction heating and studied the mass fraction of wet agglomerates. They showed that the agglomerate mass decreases with the particle exothermic rate and superficial gas velocity and increases with the liquid injection rate.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al. 20 designed a fluidized bed coupled with electromagnetic induction heating and studied the mass fraction of wet agglomerates. They showed that the agglomerate mass decreases with the particle exothermic rate and superficial gas velocity and increases with the liquid injection rate.…”
Section: Introductionmentioning
confidence: 99%